Interactive Building Environments: A Case Study University Building in UAE. (2017) - Karima, Mahbouba; Altan, Hasim
Abstract: Microprocessor-based technologies are fast becoming a key instrument in building intelligent facilities. Educational sectors are sought to be one of the critical segment in the society, an environment that has a massive impact on the learning process on the growing generations. Hence, an intelligent building with integrated advanced digital technologies becomes an exemplar for the modern existing building. This paper discusses the state of intelligence levels of an existing university building in the United Arab Emirates; the building is ESTIDAMA certified. In this study, several intelligent building system indicators have been evaluated. Building structure and in the relation between interior facilities and exterior construction will be studied. Furthermore, surveys including questionnaires and interviews have been undertaken among the building management staff, the university academics and students. After identifying weaknesses in the building system through a framework adopted using eight intelligent building indicators, recommendations are proposed enhancing the existing systems and the intelligent strategies in the case study university campus to also improve both the users' performance and productivity.